Identification of CmACL genes in melon and analysis of their potential functions in fruit sugar and acid accumulation - Ren, Kaili; Kong, Weiping; Tang, Taoxia; Cheng, Hong (Frontiers in Plant Science, 2023)
Citric acid is the most important organic acid in melon and has a great influence on fruit flavor quality. ATP-citrate (pro-S) lyase (ACL) is a key regulator in the acetyl-CoA pathway and plays an important role in citric acid metabolism. In this study we analyzed the structure and phylogenetics of CmACL genes and their functions in sugar and acid accumulation in melon. A total of four CmACL genes were identified in the melon genome, and phylogenetic analysis assigned these genes into the α subfamily (CmACLα1 and CmACLα2) and the β subfamily (CmACLβ1 and CmACLβ2). Conserved motif and gene structure analyses showed that members of the same subfamily shared identical conserved motifs and gene structures, and probably have similar biological functions. Analysis of cis-acting elements revealed that CmACL promoter sequences contained regulatory elements related to light, stress, phytohormones, and growth and development, indicating that CmACL genes may be involved in melon growth and stress responses. The prediction of protein interaction network showed that CmACL proteins were closely related to the proteins belonging to tricarboxylic acid cycle, glyoxylic acid cycle and glycolytic pathway, suggesting that CmACL proteins may play an important role in sugar and acid metabolism. The expression of CmACLβ1 was significantly and positively correlated with sucrose content, and CmACLβ2 expression was significantly positively correlated with citric acid content, suggesting that CmACLβ1 and CmACLβ2 have important roles in sugar and acid accumulation in melon. Our results offer novel insights and avenues for the regulation of sugar and acid levels in melon and provide a theoretical foundation for breeding high-quality melon cultivars.